The effect of cumulative exposure with unhealthy lifestyles on the H-type hypertension among Chinese adults: a community-based, propensity-score-matched, and case–control study - Li, Ling; Wang, Jia; Li, Jing; Li, Minqi; Long, Tianyao; Zhengliu, Yangyi; Lv, Yuan; Hong, Xiuqin (Frontiers in Nutrition, 2024)
To assess whether cumulative exposure of unhealthy lifestyles is associated with HTH in Chinese adults and to explore the combination of unhealthy lifestyles.Methods: This study combined a community-based cross-sectional study with a 1:1 matched case-control study using propensity scores among adults in six randomly selected districts from Hunan Province, China. We recruited 5,258 people, of whom 4,012 met the criteria. Lifestyles and personal characteristics were collected by a questionnaire. Lifestyle score was calculated using cigarette smoking, heavy alcohol consumption, inactive exercise, unhealthy diet and abnormal BMI. HTH was defined as having a diagnosis of essential hypertension with Hcy ≥ 15 umol/L. Logistic regression models and multivariate analyses were used to explore the associations. We calculated odds ratios (ORs) and attributable risk proportion (ARP) for the association of HTH with lifestyle score. The dose-response relationship was evaluated using restricted cubic splines method.Results: Of the 4012 adults, 793 had HTH, with a population prevalence of 19.8%. In the propensity-score-matched case-control study, 1228 (614 cases and 614 controls) were included, and those with at least four unhealthy lifestyle factors had a higher risk of HTH than those with 0 unhealthy lifestyle factor (adjusted OR = 2.60, 95%CI:1.42-4.78), with an ARP of the cumulative exposure of unhealthy lifestyle was 28.23% (95% CI: 6.34-37.86%). For three unhealthy lifestyles group, the combination of heavy alcohol consumption, unhealthy diet and BMI ≥24 Kg/m 2 was most associated with HTH (OR = 7.49, 95%CI: 1.12-50.08). For four unhealthy lifestyles group, the combination of smoking, heavy alcohol consumption, unhealthy diet and BMI ≥24 Kg/m 2 had the greatest correlation with HTH (OR =3.75, 95%CI: 1.24-7.38). Notably, there was a monotonically increasing curve (J-shaped) relationship between unhealthy lifestyles and the risk of HTH (P = 0.014).Our findings suggest that there was a significant cumulative exposure effect of unhealthy lifestyles on the risk of HTH, with the largest effect combination being heavy alcohol consumption, unhealthy diet and BMI ≥24 Kg/m 2 . Targeted interventions that reducing heavy alcohol consumption, quitting smoking, promoting physical activity and a healthy diet, and keep a normal BMI could substantially reduce the burden of HTH.